2005
DOI: 10.1177/0734242x05059668
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical treatment of marble processing wastewater and the recycling of its sludge

Abstract: In the first part of this study, the treatability of marble processing wastewater by the coagulation-flocculation process was investigated. Optimum coagulant-flocculant doses for turbidity removal in wastewater from the cutting, faience and equalization processes were determined as 500, 200 and 500 ppm of Al2(SO4)3; 300, 500 and 300 ppm of FeCl3 and 600, 400 and 200 ppm of Agrofloc 100 (AGRON Water Treatment Technologies and Chemical Marketing Industry and Trade Limited Company, Izmir, Turkey), respectively. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…So these waste material needs to be utilized meaningfully in economic way. However, particular stone cutting slurry waste may have different physical and chemical properties depending on the type of the stone and on the method of generation of waste, in this research stone which used in building as a wall which mostly limestone was used [14] [15]. Table 1 it lustrates the physical & chemical characteristic of slurry samples generated from the stone cutting process for different types of stone [16] [17].…”
Section: Stone Cutting Slurry Waste (Al-khamkha Local Name)mentioning
confidence: 99%
“…So these waste material needs to be utilized meaningfully in economic way. However, particular stone cutting slurry waste may have different physical and chemical properties depending on the type of the stone and on the method of generation of waste, in this research stone which used in building as a wall which mostly limestone was used [14] [15]. Table 1 it lustrates the physical & chemical characteristic of slurry samples generated from the stone cutting process for different types of stone [16] [17].…”
Section: Stone Cutting Slurry Waste (Al-khamkha Local Name)mentioning
confidence: 99%
“…Coagulation and flocculation is a widely used physicalchemical process in wastewater treatment. Ayoub et al (2000) investigated the coagulation-flocculation of MPW, using seawater liquid bitterns as a coagulant and in another study by Arslan et al (2005) treatment efficiency was investigated using various coagulant chemicals. In small workshops, the general application for reusing of wastewaters is currently proceeded with purifying the wastewater through gravitational settling methods in pools and then including it into the process pipeline by pumping the supernatant (Solak et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These treatment methods are not available for waste of inorganic origin, such as marble processing sludge. The treatment and reuse of these wastes by various methods are important from both environmental and waste management viewpoints (Arslan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the suspended particles in recycled water may also result in pipe clogging. Arslan et al [9] also reported a research article focusing on the usability of the coagulation-flocculation process for the treatment of marble processing wastewater and the recycling of its sludge in the cement industry. However, at most of them, only marble effluents were concerned.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a 31% anionic polymer shows the best performance on the settling rate of a Bulgarian marble suspension. Arslan et al [9] also reported a research article focusing on the usability of the coagulation-flocculation process for the treatment of marble processing wastewater and the recycling of its sludge in the cement industry. According to treatment test results conducted with both coagulation and flocculation reactive uses, an anionic polyelectrolyte, Agrofloc 100, has been found to obtain the highest treatment performance compared with other reactive such as FeCl 3 and Al 2 (SO 4 ) 3 .…”
mentioning
confidence: 99%